Pollution and environmental impact in the Bay of Chancay - Cabrera Carranza, Carlos Francisco (2001)
The pollution of coastal waters of the Bay of Chancay caused by the discharge of industrial and urban runoff, has prompted the present investigation aimed to know the extent of contamination of coastal waters of the Bay of Chancay and Impacts, to propose recovery measures and environmental control. As a result of this investigation, it is known that seawater Chancay Bay presents values ​​that are well above current regulations (Water Act), leading in extreme cases to 0.00 ml / l dissolved oxygen, 120 mg / l BOD5, 0.00 bits / ind. diversity, among others, confirming a high pollution.